Koszty i opłacalność produkcji porzeczki czarnej w zależności od metody zbioru i powierzchni plantacji - Rymuza, Katarzyna; Brzozowski, Piotr; Grużewska, Agata (Zeszyty Naukowe SGGW - Ekonomika i Organizacja Gospodarki Żywnościowej, 2012)
The work presents an analysis of blackcurrant harvest time, profitability and cultivation profitability threshold when harvest was performed manually or mechanically by means of a tractor-mounted or self-propelled harvester. It has been demonstrated that mechanical harvest reduces both the harvest time and production costs as a result of which the cultivation becomes profitable. The minimum area under blackcurrant, which generates profit, is 0.39 ha for a tractor-mounted harvester and 0.35 ha for a self-propelled harvester.